Catechin-driven dual metabolic modulation enhances docosahexaenoic acid biosynthesis and oxidative stability in Schizochytrium sp - Chengxi Zhang; Zifan Zhang; Yuxuan Chen; Yingfeng Li; Guang Yang; Xiaoman Sun; Wang Ma (Bioresource Technology, 2027)

Spring drought variability in Yunnan within Southwest China from 1580s to 2020s and its impacts on social unrest - Qian Li; Yinxian Shi; Zhenhua Li; Bin Liu; Hua Huang; Xuefei Yang; Jianchu Xu; Yingfeng Bi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

A fully bio-based stage-evolved adhesive via supramolecular-covalent network for high-performance reed structural composites - Yuhui Huang; Meng Li; Kui Li; Yan Qing; Lei Li; Yingfeng Zuo; Yiqiang Wu (Chemical Engineering Journal, 2026)

Functional interaction between Bacillus velezensis D103 and maize reveals a microbial mechanism for drought stress mitigation via photosynthesis and sugar metabolism - Yating Zhang; Zhenqiang Feng; Yanling Guo; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Bo Zhang; FangFang Yu; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; et al. (Plant Science, 2026)

Mg hydrogen generator based intelligent responsive stent for in situ therapy of reflux esophagitis - Guokai Zeng; Junjie Liang; Yuxuan Zhang; Guofeng Zeng; Xiaoying Li; Qiansha Luo; Bingjun Wu; Yuxin Tang; Jiazheng Chen; Shuhan Zhou; Fang Qin; Qi He; et al. (Chemical Engineering Journal, 2026)

Exposure to polycyclic aromatic hydrocarbons during maternal pregnancy: Effects of DNA damage on neural tube defects in offspring - Xiaoqian Jia; Yingfeng Gao; Yuan Li; Ruiwei Xu; Lei Jin; Linlin Wang; Aiguo Ren; Le Zhang; Yali Zhang; Shanshan Lin; Jicheng Gong; Zhiwen Li (Journal of Hazardous Materials, 2026)

Separation of vanadium and molybdenum from a sulfuric acid leachate - Bingxu Chen; Chunliu Li; Huaijiang Wang; Ruishu Wang; Yingfeng Cuan; Haojie Meng; Bingwu Chu (Hydrometallurgy, 2026)

Photoresponsive MXene/HKUST-1@CuS antimicrobial nanosheets towards efficient solar-driven water evaporation and biofilm eradication - Yingfeng Wang; Ming Huang; Maoli Yin; Wei Li; Xun Zhang; Xiaojuan Li; Gang Li (Journal of Environmental Chemical Engineering, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Regulation of air-sea CO2 flux and aragonite saturation state in coral reef ecosystems along the eastern coast of Hainan Island, China - Wei Yang; Zijia Zheng; Peiqiang Zhuang; Jianhang Zhang; Wei Deng; Shengyong Li; Yanmei Liu; Ming He; Yingfeng Chen; Bingbing Yu; Xinxin Xu; Xinxing Li; et al. (Marine Pollution Bulletin, 2026)

Prenatal exposure to mixtures of metals and metalloids and risk of spontaneous preterm birth: Critical exposure windows and susceptibility factors - Ruiwei Xu; Yi Zhang; Yingfeng Gao; Le Zhang; Bin Wang; Xiaoqian Jia; Min Xu; Zhiwen Li; Jicheng Gong (Journal of Hazardous Materials, 2026)

Preliminary application of synchrotron time-resolved SAXS in in-situ study of dust explosion - Haijuan Wu; Jiahao Liu; Xiaolan Ji; Wenmin Li; Longlong Yang; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Xiong Cao; Yixin Zhao (Fuel, 2026)

Bacillus velezensis D103 enhances maize drought tolerance via ROS-scavenging and phenylpropanoid pathway activation - Yating Zhang; Yingfeng An; Zhiyong Zhang; Xinyue Bi; Fangfang Yu; Bo Zhang; Tong Bi; Faryal Babar Baloch; Jianjia Miao; Yunjiao Wang; Ning Zhang; Bingxue Li (Plant Cell Reports, 2026)

Prediction of critical volatile organic compounds and identification of flavor intensity in Gastrodia elata under different preparation methods based on NIR and FTIR feature variables - Yingfeng Zhong; Jieqing Li; Honggao Liu; Yuanzhong Wang (Food Research International, 2025)

Tanshinone IIA ameliorates pancreatic injury in type 2 diabetic mice by modulating inflammation and endoplasmic reticulum stress via the IL-6/JAK2/STAT3 pathway - Yingfeng Li; Desheng Wang; Yuhang Liu; Chenyang Liu; Meixi Chen; Jingqi Li; Zunqiu Wu; Ning Wu (Functional & Integrative Genomics, 2025)

What is the relationship between urban heat island (UHI) effect and urban surface parameter (USP) at micro-scale? A case study in Gulangyu, China - Yuan Li; Yingfeng Wang; Mengsheng Yang; Yanan Du; Jingge Liu (Sustainable Cities and Society, 2025)

Massive carbon inputs from fish farming reduce carbon sequestration capacity in a macroalgae mariculture area - Wei Yang; Yingxu Wu; Yanmei Liu; Peiqiang Zhuang; Chenglong Li; Jianhang Zhang; Yingfeng Chen; Yanpei Zhuang; Hongyang Lin; Huaji Qiu; Youjun Huang; Weijie Qiu; et al. (Marine Environmental Research, 2025)

In situ study of the effect of ignition delay time on the lignite dust explosion using synchrotron radiation time-resolved SAXS - Xiaolan Ji; Jiahao Liu; Haijuan Wu; Longlong Yang; Wenmin Li; Yingfeng Sun; Qingfeng Qin; Zhihong Li; Lili Dong; Yuanyang Wang; Yixin Zhao; Xiong Cao; et al. (Fuel, 2025)

Seismic Prediction of Shallow Unconsolidated Sand in Deepwater Areas - Jiale Chen; Yingfeng Xie; Tong Wang; Haoyi Zhou; Zhen Zhang; Yonghang Li; Shi Zhang; Wei Deng (Journal of Marine Science and Engineering, 2025)
Recently, shallow gas fields and hydrate-bearing sand in the deepwater area of the northern South China Sea have been successively discovered, and the accurate prediction of shallow sands is an important foundation. However, most of the current prediction methods are mainly for deep oil and gas reservoirs. Compared with those reservoirs with high degree of consolidation, shallow sandy reservoirs are loose and unconsolidated, whose geophysical characteristics are not well understood. This paper analyzes the logging data of shallow sandy reservoirs recovered in the South China Sea recently, which show that the sand content has a significant influence on Young’s modulus and Poisson’s ratio of the sediments. Therefore, this paper firstly constructs a new petrophysical model of unconsolidated strata targeting sandy content and qualitatively links the mineral composition and the elastic parameters of the shallow marine sediments and defines a new indicator for sandy content: the modified brittleness index (MBI). The effectiveness of MBI in predicting sandy content is then verified by measured well data. Based on pre-stack seismic inversion, the MBI is then inverted, which will identify the sandy deposits. The method proposed provides technical support for the subsequent shallow gas and hydrate exploration in the South China Sea.

Large language models for diabetes training: a prospective study - Haoxuan Li; Zehua Jiang; Zhouyu Guan; Yuqian Bao; Yuexing Liu; Tingting Hu; Jiajia Li; Ruhan Liu; Liang Wu; Di Cheng; Hongwei Ji; Yong Wang; et al. (Science Bulletin, 2025)

Mechanism of anti-hepatitis potential of Tagetes erecta L.: UPLC-Q-TOF-M S/MS, network pharmacology, molecular docking and in vitro experimental validation - Jiangning Peng; Zhenxia Zhao; Zhiqian Yuan; Yingfeng Du; Hong Wang; Yunhe Lian; Xinyi Yang; Hui Li (Next Research, 2025)

How to classify microclimates more validly and finely? A novel method for mapping local climate zone (LCZ) on micro-scales - Mengsheng Yang; Yuan Li; Yanan Du; Yingfeng Wang; Jingge Liu; Lijuan Yang; Jingxiong Huang (Sustainable Cities and Society, 2025)

Multidimensional effects of green waste vermicomposting on cadmium contaminated soil ecosystems: From physicochemical properties to microbial communities - Li Huang; Yurui Meng; Boyou Pan; Bogui Pan; Junyu Wei; Jinhua Ding; Yingfeng Deng; Xianglan Su; Ziwei Yuan; Menghao Zhang (Journal of Hazardous Materials, 2024)

Toward the bioactive potential of myricitrin in food production: state-of-the-art green extraction and trends in biosynthesis - Yaqian Geng; Yingfeng Xie; Wei Li; Yao Mou; Fang Chen; Jianbo Xiao; Xiaojun Liao; Xiaosong Hu; Junfu Ji; Lingjun Ma (Critical Reviews in Food Science and Nutrition, 2024)

Mixed matrix membranes for gas separations: A review - Zhenhua Niu; Naiyong He; Yingfeng Yao; Aijun Ma; Enyu Zhang; Liang Cheng; Yuliang Li; Xingwu Lu (Chemical Engineering Journal, 2024)

What is the outdoor thermal comfort (OTC) threshold in Gulangyu, China: An empirical study - Mengsheng Yang; Yuan Li; Yanan Du; Yingfeng Wang; Wenyi Fei; Jingxiong Huang; Jiaqi Liang (Urban Climate, 2024)

Achieving sustainable and highly efficient wood bonding through synergistic plant root-driven penetration mode with a hyperactive interface - Xiaoqian Bi; Yuan Zhang; Ping Li; Yan Wang; Yiqiang Wu; Yingfeng Zuo (Chemical Engineering Journal, 2024)

Large language models for diabetes care: Potentials and prospects - Bin Sheng; Zhouyu Guan; Lee-Ling Lim; Zehua Jiang; Nestoras Mathioudakis; Jiajia Li; Ruhan Liu; Yuqian Bao; Yong Mong Bee; Ya-Xing Wang; Yingfeng Zheng; Gavin Siew Wei Tan; et al. (Science Bulletin, 2024)

A Fluorescence Biosensor Based on Carbon Quantum Dots Prepared from Pomegranate Peel and T-Hg2+-T Mismatch for Hg2+ Detection - Weiqin Zhao; Chun Huang; Xiyu Guo; Youyu Zhu; Yuangang Li; Yingfeng Duan; Jie Gao (Journal of Fluorescence, 2024)

Genomic sequencing revealed recombination event between clade 1 and clade 2 occurs in circulating varicella-zoster virus in China - Jia Li; Dan Wang; Libin Qi; Yuewu Yang; Jiawei Pei; Yangchao Dong; Yuan Wang; Min Yao; Fanglin Zhang; Yingfeng Lei; Linfeng Cheng; Wei Ye (Brazilian Journal of Microbiology, 2024)

Rewiring Bacillus subtilis and bioprocess optimization for oxidoreductive reaction-mediated biosynthesis of D-tagatose - Guoyan Zhang; Yingfeng An; Hossain M Zabed; Junhua Yun; Amreesh Parvez; Mei Zhao; Cunsheng Zhang; Yuvaraj Ravikumar; Jia Li; Xianghui Qi (Bioresource Technology, 2023)

Degraded frozen soil and reduced frost heave in China due to climate warming - Zhongqiong Zhang; Miao Li; Zhi Wen; Zhiqiang Yin; Yingfeng Tang; Siru Gao; Qingbai Wu (Science of The Total Environment, 2023)

Molecular-level topological deep cross-fusion strategy towards organic–inorganic lightweight composites - Long Zheng; Yiqiang Wu; Xingong Li; Yingfeng Zuo (Chemical Engineering Journal, 2023)

Dual drug-loaded calabash-like nanomotor as an active therapeutic for enhanced chemo-photothermal therapy of orthotopic glioblastoma - Huaan Li; Xiaoting Zhang; Jiajun Miao; Zhengyu Shi; Ziqi Li; Minjun Wen; Limeng Wang; Jiayuan Liang; Junbin Gao; Yicheng Ye; Hao Tian; Fei Peng; et al. (Chemical Engineering Journal, 2023)

High-zeta-potential accelerates interface charge transfer in lithium anodes via MXene-graphdiyne heterojunction layers - Lu Sun; Meifeng Li; Jianan Gu; Yingfeng Li; Jinzhang Liu; Yan Li; Meicheng Li (Chemical Engineering Journal, 2023)

Light-driven micromotor swarm induced in-situ polymerization and synergistic photothermal therapy - Zeqi Li; Shaoming Fu; Huaan Li; Bin Chen; Dazhi Xie; Dongmei Fu; Ye Feng; Chao Gao; Suyi Liu; Daniela A. Wilson; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2023)

New insights into enhanced electrochemical advanced oxidation mechanism of B-doped graphene aerogel: Experiments, molecular dynamics simulations and DFT - Wenwen Gu; Mingwang Yang; Zhuang Chen; Ting Cao; Yimei Zhang; Yingfeng Li; Ranran Zhang (Journal of Hazardous Materials, 2023)

Experimental Study on the Influence Mechanism of Coal–Rock Fracture Differential Deformation on Composite Permeability - Yulin Li; Cun Zhang; Yingfeng Sun; Ziyu Song; Lei Zhang (Natural Resources Research, 2022)

Changes in Copper, Zinc, Arsenic, Mercury, and Lead Concentrations in Rat Biofluids and Tissues Induced by the “Renqing Changjue” Pill, a Traditional Tibetan Medicine - Lan Zhang; Caidan Rezeng; Yingfeng Wang; Zhongfeng Li (Biological Trace Element Research, 2021)

Effects of Drying-Rewetting Frequency on Vertical and Lateral Loss of Soil Organic Carbon in a Tidal Salt Marsh - Juanyong Li; Wendi Qu; Guangxuan Han; Feng Lu; Yingfeng Zhou; Weimin Song; Baohua Xie; Franziska Eller (Wetlands, 2020)

Study of failure mechanism of bottom-hole rock mass approaching a gas-fractured zone during nitrogen drilling - Luo Chengbo; Jiang Zujun; Li Gao; He Long; Ou Biao; Meng Yingfeng; Xiao Guoyi; Yan Yancheng; Wang Xiyong (Arabian Journal of Geosciences, 2020)

Clinical characteristic of 15 cases of cryptococcal meningitis treated with Ommaya reservoir - Yingfeng Wan; Xinwei Li; Yirong Wang; Yunsong Yu; Shuxu Yang (Acta Neurologica Belgica, 2020)

Ring-widths of Abies at tree-line ecotone reveal three centuries of early winter season temperature changes in Yunnan, China - Yingfeng Bi; Whitney Cory; Zenxin Fan; Jingchao Yang; Zhikun Wu; Wei Huang; Jianwen Li; Xuefei Yang (Climate Dynamics, 2020)
Variation in winter temperature is less well understood than in annual and summer temperatures over long timescales, particularly in low-latitude (0–30° N) montane regions with large spatial and topographic heterogeneity. Understanding these variations could be critical for forest manageemnt in these important tree growing regions. We collected tree-ring cores from Yunnan Province in montane southwest China, to determine how winter temperature has varied in the past and to explore its possible drivers in this region. Six highly correlated site chronologies were combined into a long and well-replicated regional composite (RC) chronology. The RC chronology correlated strongest with mean early winter season temperature (EWST) from November to January during 1959–2015. We applied RC chronology to reconstruct EWST from 1653 to 2015. The reconstruction shows five relatively warm historic intervals (1658–1718, 1743–1755, 1771–1791, 1929–1959, and 1995–2015) and cold intervals (1720–1742, 1792–1852, 1860–1883, 1905–1928, and 1960–1994). The 1950s with six anomalous warm seasons and 1980s with five anomalous cold seasons were the warmest and coldest decades, respectively. The EWST reconstruction generally agreed with other winter temperature reconstructions from nearby areas and with historical documents. Atlantic Multidecadal Oscillation (AMO) might be a key forcing of multidecadal winter temperature variations in montane southwest China over the past three and half centuries. Both warm and cold temperature periods coincide with respective positive and negative phases of AMO. Besides, the cold intervals during the nineteenth and twentieth centuries may also have been influenced by large volcano eruptions in low-latitude regions of south and east Asia. Our EWST reconstruction not only improves our understanding of the trends and variations of winter climate history, but also supports planning for resilience in conservation, agriculture, and forestry management in montane southwest China into the future.

An experimental study on stress sensitivity of tight sandstone gas reservoirs during nitrogen drilling - Meng Yingfeng; Luo Chengbo; Li Gao; Liu Houbin (Arabian Journal of Geosciences, 2019)

Ring-widths of the above tree-line shrub Rhododendron reveal the change of minimum winter temperature over the past 211 years in Southwestern China - Yingfeng Bi; Jianchu Xu; Jinchao Yang; Zongshan Li; Aster Gebrekirstos; Eryuan Liang; Shibao Zhang; Yang Yang; Yongping Yang; Xuefei Yang (Climate Dynamics, 2017)

An Anisotropic Strength Model for Layered Rocks Considering Planes of Weakness - Xiangchao Shi; Xu Yang; Yingfeng Meng; Gao Li (Rock Mechanics and Rock Engineering, 2016)

Putrescine protects hulless barley from damage due to UV-B stress via H2S- and H2O2-mediated signaling pathways - Qien Li; Zhaofeng Wang; Yanning Zhao; Xiaochen Zhang; Shuaijun Zhang; Letao Bo; Yao Wang; Yingfeng Ding; Lizhe An (Plant Cell Reports, 2016)

Weakening laws of rock uniaxial compressive strength with consideration of water content and rock porosity - Xiangchao Shi; Wuqiang Cai; Yingfeng Meng; Gao Li; Ke Wen; Yunrong Zhang (Arabian Journal of Geosciences, 2016)

Effects of Working Angle on Pneumatic Down-the-hole Hammer Drilling - Zhi Zhao; Yingfeng Meng; Yongjie Li; Xiangchao Shi; Chengliao Xiang (Rock Mechanics and Rock Engineering, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

15 N ‐ and 2 H proteomic stable isotope probing links nitrogen flow to archaeal heterotrophic activity - Nicholas B. Justice; Zhou Li; Yingfeng Wang; Susan E. Spaudling; Annika C. Mosier; Robert L. Hettich; Chongle Pan; Jillian F. Banfield (Environmental Microbiology, 2014)
Summary Understanding how individual species contribute to nutrient transformations in a microbial community is critical to prediction of overall ecosystem function. We conducted microcosm experiments in which floating acid mine drainage ( AMD ) microbial biofilms were submerged – recapitulating the final stage in a natural biofilm life cycle. Biofilms were amended with either 15 NH 4 + or deuterium oxide ( 2 H 2 O ) and proteomic stable isotope probing ( SIP ) was used to track the extent to which different members of the community used these molecules in protein synthesis across anaerobic iron‐reducing, aerobic iron‐reducing and aerobic iron‐oxidizing environments. S ulfobacillus spp. synthesized 15 N ‐enriched protein almost exclusively under iron‐reducing conditions whereas the L eptospirillum spp. synthesized 15 N ‐enriched protein in all conditions. There were relatively few 15 N ‐enriched archaeal proteins, and all showed low atom% enrichment, consistent with A rchaea synthesizing protein using the predominantly 14 N biomass derived from recycled biomolecules. In parallel experiments using 2 H 2 O , extensive archaeal protein synthesis was detected in all conditions. In contrast, the bacterial species showed little protein synthesis using 2 H 2 O . The nearly exclusive ability of A rchaea to synthesize proteins using 2 H 2 O may be due to archaeal heterotrophy, whereby A rchaea offset deleterious effects of 2 H by accessing 1 H generated by respiration of organic compounds.